Ectopic Variceal Bleeding From Colonic Stoma. Issue 2 (January 2015) - Wang, Lei; Zhou, Jiao-lin; Yang, Ning; Zhang, Guan-nan; Lu, Jun-yang; Xiao, Yi; Qiu, Hui-zhong; Wu., Yinyuan
<x xml:space="preserve">Abstract</x> Abstract Parastomal variceal bleeding is a rare complication of portal hypertension, which often occurs in a recurrent manner and might be life-threatening in extreme situations. Treatment options vary, and no standard therapy has been established. Herein, we report 2 such cases. The first patient suffered from parastomal variceal bleeding after Hartmann procedure for rectal cancer. Stomal revision was performed, but bleeding recurred 1 month later. The second patient developed the disease after Miles procedure for rectal cancer. Embolization via the percutaneous transhepatic approach was performed using the Onyx liquid embolic system (LES) (Micro Therapeutics Inc, dba ev3 Neurovascular) in combination with coils, and satisfactory results were obtained after a 4-month follow-up. Our cases illustrate that surgical revision should be used with caution as a temporary solution due to the high risk of rebleeding, whereas transhepatic embolization via the Onyx LES and coils could be considered a safe and effective choice for skillful managers.